THE INFLUENCE OF STUDENTS' LEARNING DISCIPLINE ON LEARNING ACHIEVEMENT IN SOCIAL STUDIES SUBJECT AMONG GRADE VII STUDENTS AT SMP NEGERI 10 PEMATANGSIANTAR - Theresi; Anggun Tiur Ida Sinaga; Injen Pardamean Butabutar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the effect of learning discipline on students’ academic achievement. The research instruments used were a learning discipline questionnaire and an academic achievement questionnaire, both of which had been tested for validity and reliability with satisfactory results. The normality test using the Kolmogorov-Smirnov method indicated that the data were normally distributed, with a significance value of 0.200 greater than 0.05. Simple linear regression analysis produced the equation Y = 60.135 + 0.258X, which demonstrates a positive relationship between learning discipline and academic achievement. The regression significance test showed that the t-value of 11.417 was greater than the t-table value of 1.67203 at a 5% significance level, and the significance value of 0.002 was less than 0.05, indicating that learning discipline has a positive and significant effect on academic achievement. The coefficient of determination (R Square) was 0.150, meaning that learning discipline contributed 15% to academic achievement, while the remaining 85% was influenced by other factors outside the scope of this study.